Correlation between climate variables and incidence coefficients of arboviroses in Ribeirão Preto, São Paulo, Brazil (Research, Society and Development, 2022)
Objective: To analyze the correlation between vector control indices, climatic variables and incidence coefficients of dengue, zika and chikungunya in the city of Ribeirão Preto, SP. Method: Ecological study, with data obtained from the Information System on Notifiable Diseases, Environmental Surveillance and the page of the Integrated Center for Agrometeorological Information. Data were analyzed using Spearman's correlation (ρ) and generalized linear model with negative Binomial distribution and identity link function. Results: Temperature had a positive relationship with the coefficient of dengue incidence, p